2017
DOI: 10.1186/s12911-017-0418-4
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition of multiple sclerosis using natural language processing of the electronic health record

Abstract: BackgroundDiagnostic accuracy might be improved by algorithms that searched patients’ clinical notes in the electronic health record (EHR) for signs and symptoms of diseases such as multiple sclerosis (MS). The focus this study was to determine if patients with MS could be identified from their clinical notes prior to the initial recognition by their healthcare providers.MethodsAn MS-enriched cohort of patients with well-established MS (n = 165) and controls (n = 545), was generated from the adult outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 52 publications
2
57
0
Order By: Relevance
“…The main objectives of studies included in this review (Table 2) were to capture or detect symptoms (n ¼ 10) 20,23,27,30,31,35,[37][38][39]42 ; identify, classify, or characterize disease (n ¼ 8) 21,22,24,25,33,43,45,46 ; study adverse drug (n ¼ 5) 32,34,36,41,44 or vaccine (n ¼ 1) 29 events; and identify or detect readmission (n ¼ 1), 26 presence of a device (n ¼ 1), 28 or unplanned clinical encounters (n ¼ 1). 40 Approximately 52% (n ¼ 14) of studies presented symptom-related information as a primary outcome.…”
Section: Study Purpose and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objectives of studies included in this review (Table 2) were to capture or detect symptoms (n ¼ 10) 20,23,27,30,31,35,[37][38][39]42 ; identify, classify, or characterize disease (n ¼ 8) 21,22,24,25,33,43,45,46 ; study adverse drug (n ¼ 5) 32,34,36,41,44 or vaccine (n ¼ 1) 29 events; and identify or detect readmission (n ¼ 1), 26 presence of a device (n ¼ 1), 28 or unplanned clinical encounters (n ¼ 1). 40 Approximately 52% (n ¼ 14) of studies presented symptom-related information as a primary outcome.…”
Section: Study Purpose and Data Sourcesmentioning
confidence: 99%
“…Free-text narratives were primarily from EHRs (n ¼ 13) 20,22,24,26,29,31,35,37,38,41,42,45,46 and data repositories (n ¼ 12). 21,23,25,27,28,32,33,36,39,40,43,44 Free-text narratives used in the 2 remaining studies were obtained from paper records converted into electronic free text 30 and Informatics for Integrating Biology & the Bedside Challenge datasets. 34 Narratives represented both inpatient (eg, admission documents, discharge summaries, emergency department documents, progress notes, nursing narratives) and outpatient (eg, primary care and specialty clinic documents, mental health encounters) settings and were written by various members of the clinical care team (eg, physicians, nurses).…”
Section: Study Purpose and Data Sourcesmentioning
confidence: 99%
“…Electronic health record (EHR) systems are a type of health information technology (HIT) that has been widely proposed as a mechanism for improving the quality and positive impact of health care services [ 1 - 4 ]. Research suggests that a well-implemented and fully-integrated EHR systems can promote complete record-keeping and more efficient access to documentation, facilitating information sharing and better coordination of care [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic health record (EHR) systems are a type of health information technology (HIT) that has been widely proposed as a mechanism for improving the quality and positive impact of health care services [ 1 - 4 ]. Research suggests that a well-implemented and fully-integrated EHR systems can promote complete record-keeping and more efficient access to documentation, facilitating information sharing and better coordination of care [ 1 , 5 , 6 ]. Other proposed, but less well-validated, benefits of EHR systems include: (1) facilitating the use of standardized assessments that can promote progress monitoring, (2) better linkage to evidence-based interventions, (3) more effective communication between providers and supervisors, and (4) use of data to promote quality improvement and research [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that later initiation of disease‐modifying drug treatments is associated with a greater likelihood of relapse compared with earlier initiation . A study from Cleveland Clinic using EMR data of MS patients identified three subgroups of patients with different depression level trajectories, and another study applied a natural language processing (NLP)‐based classification on clinical notes to identify MS patients before the initial recognition by their healthcare providers …”
Section: Use Of Electronic Medical Records In Multiple Sclerosis Resementioning
confidence: 99%